Education to enhance halal and healthy food literacy in early childhood at Aisyiyah Bustanul Athfal Panongan 1 Kindergarten - Rusdiana, Nita; Utami, Fitria Budi; Lestari, Maya; Ma'sum, Ma'sum; Aisha, Dewi; Maharani, Clarisa Xtri; Anzoya, Aulia (Universitas Muhammadiyah Magelang, 2025)
In Indonesia, halal labeling is crucial for Muslim consumers, but understanding varies, especially among early childhood children. This community service activity aims to improve the understanding of halal and healthy food concepts. The activity was carried out using interactive education methods (storytelling, singing, halal logo demonstrations) at TK Aisyiyah Bustanul Athfal Panongan 1. The results of the activity showed an increase in children's understanding of halal food concepts and the Indonesian halal logo. The interactive education conducted proved to be effective, engaging, and able to help children remember the halal concept in a fun way. This activity emphasizes the importance of the role of teachers, parents, and educational institutions in introducing the concept of halal food from an early age, to build awareness and positive habits towards food consumption that aligns with Islamic principles.